Chief of station [videorecording (DVD)] - Murray, Sean (Vertical, 2024)
After learning the untimely death of his wife was not accidental, a former CIA Station Chief is forced back into the espionage underworld, teaming up with an adversary to unravel a conspiracy that challenges everything he thought he knew.